2017
DOI: 10.1016/j.jpain.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Pain Modulation in Torture Survivors: The Mediating Effect of PTSD

Abstract: This article presents the mediation effect of PTSD trajectory on pain modulation among trauma survivors suggesting that it is the duration and severity of PTSD/distress, rather than the exposure to trauma per se, that influence the perception and modulation of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…This finding is theoretically important because congruent with a PTSD diagnosis is a related propensity to experience chronic pain as suggested in previous theoretical models of the PTSD–pain relationship (Asmundson et al, 2002). Another interpretation of the importance of PTSD and its relationship to pain was suggested in a recent study of torture victims (Defrin, Lahav, & Solomon, 2016) where it is suggested that PTSD moderated the relationship between trauma exposure and pain by altering pain modulation.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is theoretically important because congruent with a PTSD diagnosis is a related propensity to experience chronic pain as suggested in previous theoretical models of the PTSD–pain relationship (Asmundson et al, 2002). Another interpretation of the importance of PTSD and its relationship to pain was suggested in a recent study of torture victims (Defrin, Lahav, & Solomon, 2016) where it is suggested that PTSD moderated the relationship between trauma exposure and pain by altering pain modulation.…”
Section: Discussionmentioning
confidence: 97%
“…Models including both bottom-up and top-down mechanisms have been suggested (Defrin, Lahav, & Solomon, 2017). Bottom-up influences generally pertain to the cascade of consequences triggered by peripheral tissue damage, such as the experience of pain due to nociceptive stimuli.…”
Section: Models and Predictors For The Development Of Somatic Complaintsmentioning
confidence: 99%
“…Indeed, data supports the notion that chronic pain is ongoing and persists at nearly the same level as at the time of the initiating event (Olsen et al, 2006), and survivors have higher lifetime prevalence of psychiatric disorders (Van Ommeren et al, 2001). Psychological or physical torture may inflict ‘pain,’ but memories of pain may also be blunted as a result of impaired memory formation due to stress (Defrin et al, 2017). There seems to be a powerful interaction between pain and emotional processing: on the one hand, the level of pain predicts psychological sequelae (de C Williams and van der Merwe, 2013), while the type of psychological stress, rather than the trauma per se, has a significant effect on pain modulation and perception (Defrin et al, 2014, 2017).…”
Section: When Pain Pops Out To Conscious Awareness – Insights Frommentioning
confidence: 99%
“…Psychological or physical torture may inflict ‘pain,’ but memories of pain may also be blunted as a result of impaired memory formation due to stress (Defrin et al, 2017). There seems to be a powerful interaction between pain and emotional processing: on the one hand, the level of pain predicts psychological sequelae (de C Williams and van der Merwe, 2013), while the type of psychological stress, rather than the trauma per se, has a significant effect on pain modulation and perception (Defrin et al, 2014, 2017). “ Torture appears to induce generalized dysfunctional pain modulation that may underlie the intense chronic pain experienced by torture survivors decades after torture ”.…”
Section: When Pain Pops Out To Conscious Awareness – Insights Frommentioning
confidence: 99%